Performance of gamification strategies in obesity management: A network meta-analysis - Jowono, Josh Nathaniel; Rampengan, Derren David Christian Homenta; Lele, Juan Alessandro Jeremis Maruli Nura; Darma, Didi Setya; Willyanto, Sebastian Emmanuel; Rampengan, Jade Audrey Homenta; Kadariswantiningsih, Ika N.; Goh, Lucky Poh Wah; Empitu, Maulana A. (Acta Biomedica Atenei Parmensis, 2025)
Background and Aims: Obesity remains a global public health challenge, with conventional interventions focusing on diet and physical activity often showing limited long-term success. Gamification—applying game elements in non-game contexts—has emerged as a novel strategy to promote healthier behaviors. This study assessed the comparative effectiveness of gamification strategies in improving nutritional knowledge, physical activity, and nutritional status among individuals with overweight or obesity through a network meta-analysis. Methods: A systematic search of PubMed, ScienceDirect, Wiley, and Cochrane databases was conducted in August 2024 to identify randomized controlled trials assessing gamification interventions. Outcomes included nutritional knowledge, physical activity, and nutritional status. Risk of bias was evaluated using RoB 2.0 and certainty of evidence using GRADE. Standardized mean differences (SMD) were pooled using fixed-effects models, and a network meta-analysis compared different gamification strategies. Results: Gamification interventions showed positive trends in improving nutritional knowledge (SMD = 2.71). Significant reductions were found in BMI (SMD = -0.23). The most effective strategy was “Programme + Active Game.” Conclusions: Gamification strategies, particularly those incorporating active physical components, are associated with significant reductions in BMI. While improvements in nutritional knowledge and physical activity showed positive trends, these effects did not reach statistical significance, highlighting the need for further research to validate these outcomes.